Manuskrip Karakteristik dan Romantika Cinta Nabi Yusuf dan Siti Zulaikhah dalam Serat Yusuf Koleksi Museum Mpu Tantular Sidoarjo (Kajian Filologi: Analisis Isi) - Nafi, Moh. Iqbal; Rochimah (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2024)
Manuscripts are a valuable legacy of Indonesian ancestral culture that reflects the thoughts and feelings of the past. Manuscripts have important historical and cultural values, with various types such as hikayat, fiber, babad, and others. One example of an ancient manuscript is Serat Yusuf, which originated from Madura and is written in Pegon Arabic script. This study aims to reveal the content and characteristics of Serat Yusuf, especially in facing the temptation of Siti Zulaikhah. The diplomatic edition of the single manuscript philology method was used in editing the manuscript, with the stages of data collection, text criticism, text editing, transliteration, and content analysis. The results show that Serat Yusuf tells the life story of the Prophet Yusuf and focuses on the temptation of Siti Zulaikhah. The Prophet Joseph is portrayed as a figure with firm faith and morals, showing wisdom in facing the temptation. Philological and cultural approaches were used to understand and analyze the text. The results of this study provide an indepth understanding of the cultural values and moral messages contained in Serat Yusuf, which are relevant to be studied in the context of people's lives today.